Value-added services in the converged network. - De Serres, Y.
Now that the local market is open to competition, incumbent local exchange carriers as well as competitive LECs must not only follow the technology curve, but find a way to ride the wave of network convergence and offer innovative value-added services if they want to maintain their market share. Over the past decade, the intelligent network has been used to support value-added services. New APIs are being designed for the creation of value-added services spanning multiple domains (wireline/wireless, voice/data, public/enterprise). These APIs will not only ease the development of value-added services, but will also open service creation to third parties
Keywords: IN; Java; Competitive LEC; Converged network; Economic factors; Intelligent network; Intelligent networks; Local exchange carriers; Local market; Market competition; Network convergence; Network technology; Public/enterprise.; Public/enterprise services; Service creation; Technology curve; Value added services; Value-added services; Voice/data services; Wireline/wireless.